فاعليـة استراتيجيــة (K.W.L) فـــي تحصيل طالبات الصف الرابع العلمي فـــي مادة التربيـة الإسلاميـة (Journal of the College of Basic Education, 2025)
The research seeks to identify the effectiveness of the (K.W.L) strategy in the academic achievement of fourth-grade female students in the subject of Islamic education. In order to achieve the research goal, the researcher developed the null hypothesis and used an experimental design with The two groups were equal, and the researcher chose Nour Al-Shams Preparatory School for Girls, the school for the research sample, and determined the experimental group through random drawing. Section (B) represented the control group and was taught according to the usual method, and Section (D) represented the experimental group, which was taught according to the (K.W.L) strategy. . The researcher rewarded the two research groups in each Age in months, the level of academic achievement of the parents, and grades in the Islamic education subject for the past year. After that, the researcher determined the topics that would be studied for the first and second units of Islamic education for the fourth scientific grade. The researcher prepared study plans for both groups, as well as behavioral goals. She prepared (44) behavioral goals and presented them to a group of experts and specialists, and they were modified according to the recommendations. The researcher prepared the achievement test and also presented it to the experts, and their performance was taken into consideration and modified. It now contained (30) multiple-choice type items because it is characterized by objectivity and comprehensiveness. The test items were analyzed by means of discriminatory power, difficulty coefficient, and effectiveness of incorrect alternatives, and were studied. The researcher The two research groups, after the end of the experiment, conducted the test for the students of the two research groups, and the researcher corrected the students’ answers, and then the results were processed statistically by using the t-test for two independent samples, which showed that there was a statistically significant difference between the two research groups at a significance level (0.05) in favor of the experimental group. So the researcher concluded that The K.W.L strategy has a clear impact on the female students of the experimental group. The researcher recommended paying attention to modern strategies, including (K.W.L.), and the researcher suggested holding educational courses for teachers showing the importance of modern strategies and how to benefit from them in teaching subjects, including Islamic education.